CEPA INDONESIA – SOUTH KOREA AND ITS IMPACT ON THE DEVELOPMENT OF INDONESIA’S ELECTRIC VEHICLE INDUSTRY AND INTERNATIONAL TRADE - Mustafa Zen, Equal Huda; Cahyaningratri, Cahyaningratri; Wicaksono, Bimo Suryo (Faculty of Economics and Business Diponegoro University, 2024)
ABSTRACT The electric vehicle (EV) and EV battery (EVB) industry in Indonesia is in its early stages of development, with key players such as Indonesia Battery Corporation (IBC), an Indonesian-based battery company, and Hyundai, South Korea’s largest automotive manufacturer. This research applies the National Competitive Advantage theory to explore the impact of the Indonesia-South Korea Comprehensive Economic Partnership Agreement (IK-CEPA) on this emerging sector. This research examines the impact of the IK-CEPA on Indonesia's nascent electric vehicle (EV) and EV battery (EVB) industry. Key influencers for EV and EVB growth include government incentives, charging infrastructure, green energy adoption, and fluctuating gas prices. Open-ended interviews were conducted with appropriate respondents working in related industry. Findings reveal that current government incentives boost EV adoption, yet the broader EV and EVB sector in Indonesia remains emergent. The IK-CEPA bolsters the industry by fostering economic collaboration between Indonesia and South Korea, attracting significant investments from leading South Korean EV and EVB corporations. However, the industry's advancement is curtailed by inadequate charging infrastructure, particularly outside Jakarta. For widespread EV adoption, consumer concerns such as charging facilities, market variety, and total cost of ownership need addressing. This study advocates for an internalized value chain in Indonesia's EV sector, emphasizing cost efficiency and attracting foreign EV enterprises. Through the IK-CEPA, the mutual benefits of technology exchange, cost reductions, and market accessibility can considerably enhance Indonesia's position in the global EV industry